UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI MEDIA PEMBELAJARAN FILM ANIMASI PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI (PAI-BP) DI KELAS VI SD NEGERI 32 PALEMBANG - Sugiarto Sugiarto; Alimron Alimron; Maryamah Maryamah; Ermila Katra (GURUKU, 2023)
The purpose of this study is to find out the efforts to improve student learning outcomes through learning media of animated films in the learning of Islamic religious education and morals (PAI & BP) in class VI SD Negeri 32 Palembang in the subject of PAI-BP, the model in this study uses the Kurt Lewin's research consisted of 4 stages namely; planning, implementation of action, observation and reflection. The results of this study can be explained as follows: 1) in the application of the Animation Film method there is an increase in student learning outcomes in each cycle, this can be proven for learning outcomes in cycle I reaching a percentage of 70.37%, while in cycle II learning outcomes achieving a percentage of 100% there increase in student learning outcomes in each cycle. Evidenced by the class average value in cycle I of 74.07 and in cycle II of 86.66 so that in cycle II it was declared successful because it had achieved performance indicators.